2012
DOI: 10.7763/ijtef.2012.v3.173
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Rural Tourism: Perspectives from the Local Communities

Abstract: Abstract-Malaysian rural tourism is composed of a large number of rural communities, each with distinct and varied assets. Within Malaysia, it is noticeably that tourism demand drivers play an important part in generating trips to rural tourism areas. Rural tourism enables tourists to reunite with nature and the culture of the destinations, and that it contributes to the economic and social recovery of the rural areas, as well as to the conservation of the environment and the spreading of local cultures. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
1
22
0
1
Order By: Relevance
“…In fact, it makes sense also, as it can be achieved more easily than the other products and without any investment and training, and helps to compensate for the lack of the others in the short term. Friendliness of local people was also described an important complementary factor in rural tourism from the local communities' perspectives in different cultures (LO et al, 2012) and host-guest relations have been reported to significantly increase the quality of rural experience (KASTENHOLZ et al, 2018). Previous studies where positioning rural tourism were investigated suggested that among the different dimensions of rural areas, visitors should look for culture associated with localness which plays an important role in rural tourism destination.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it makes sense also, as it can be achieved more easily than the other products and without any investment and training, and helps to compensate for the lack of the others in the short term. Friendliness of local people was also described an important complementary factor in rural tourism from the local communities' perspectives in different cultures (LO et al, 2012) and host-guest relations have been reported to significantly increase the quality of rural experience (KASTENHOLZ et al, 2018). Previous studies where positioning rural tourism were investigated suggested that among the different dimensions of rural areas, visitors should look for culture associated with localness which plays an important role in rural tourism destination.…”
Section: Resultsmentioning
confidence: 99%
“…In Sarawak, the Dayak homestay programme is mostly based on cultural immersion, handicraft making, local cuisine and nature, with the unique and major attracting factor being the longhouse lifestyle itself. In fact, the programme is considered to be a community based entrepreneurship initiative (Agarwal et al, 2003), although as argued by Mascardo (2008), it is associated with social impacts and greater opportunities for local communities to be involved apart from acting as an agent for social-cultural and economic development, especially on rural community development (Ibrahim & Razzaq, 2009;Lo et al, 2012). On the contrary, Mascardo (2008) also argues that community-based tourism is not, however, universally hailed as a positive option for the development of rural regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Certainly, within the perspective of homestay businesses, a number of scholars have studied the small rural tourism industry in Malaysia and discussed the potential of the homestay programme (Hamzah, 2008;Ibrahim & Razzaq, 2009;Lo et al, 2012;Razzaq et al, 2011). Nevertheless, most of these studies focused on the community participation, including the economic, social and environmental impacts derived from the activity.…”
Section: Introductionmentioning
confidence: 99%
“…As such, digital marketing can bypass the physical barriers of transmitting information transmission to the intended market, a feature particularly important for rural tourism destinations. In Malaysia, ICT in general, and telecentres in particular, have helped to advance tourism at rural destinations (Lo, Mohamad, Songan, & Yeo, 2012). More recently, the Sarawak statement government has, via the setting up of the Digital Sarawak Centre of Excellence (DSCOE), led an initiative towards the digital transformation of the state economy.…”
Section: Introductionmentioning
confidence: 99%